The effectiveness of government policies in abandoned building-buyers - Nur Fathin Nadhirah, Muhd Aliff (2019)
Abandoned building are the common thing happened around the world. The term ‘abandoned’ itself show that the building that has been left out or been declined for certain situation or problems. Abandoned building is one of the issue in construction industry that never be settled down until now. The abandoned building has affected many people especially the buyer of the building. Government has stepped up to create laws that would protect buyers who buy house from the developer. Act 118, Housing Development (Control and Licensing) Act 1966 amended to help those buyers in Peninsular Malaysia from become continuous victim. The literature review in this study will focused more on the causes of abandoned building (financial problem, fraud and corruption, conflict between parties, mismanagement of the construction project etc.), the possible parties that responsible in abandoned building, the economic recession and legal issue in Malaysia. The method used in this study to collect data is distributing the questionnaire survey to the people in construction industry such as developer, consultant, contractor, government and other that are related in construction industry. From the respondent’s point of view, the data been analysed to find out the effectiveness of government policies towards buyers and possible solution to solve the abandoned building issue.